Constitutional Rights of Indigenous Law Communities and Legal Politics as Means of Assessing Legal Alignments to Indigenous Law Communities - Aang Sirojul Munir (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The existence of indigenous peoples existed even before Indonesia's independence. Its existence was later recognized by the Indonesian constitution, namely the 1945 Constitution. The rights granted by the 1945 Constitution are constitutional rights owned by indigenous peoples. However, the constitutional rights can be canceled only because of an opinion that the customary law community or parts of themselves are deemed irrelevant. This constitutional right can also be disturbed by the enactment of a law. Through the legal political approach, there is no visible side of legal policy towards the existence of indigenous peoples. This is indicated by the absence of an organic law that specifically regulates the existence of indigenous peoples as mandatory laws and regulations from the content of the constitution that regulates and protects the existence of indigenous peoples and the traditional rights attached to them. Indigenous and tribal peoples also do not have configurable power to influence legal policies, such as those policies that are detrimental to them.